Take a hike! - Flowers, Luke (New York, NY : Scholastic Inc., 2020)
On a camping trip with his dog Toby, Moby Shinobi's ninja skills keep making a mess of things but when hikers get lost he leads a team to save them.
Keywords: Stories in rhyme; Camping -- Juvenile fiction; Hiking -- Juvenile fiction; Ninja -- Juvenile fiction; Dogs -- Juvenile fiction; Stories in rhyme; Camping -- Fiction; Hiking -- Fiction; Ninja -- Fiction; Dogs -- Fiction